Designing the new European Union - Berger, Helge; Moutos, Thomas; CESifo (Amsterdam ; Boston : Elsevier, 2007)
This volume is based on papers delivered at the second CESifo-Delphi Conferences (Munich, November 2003, and Delphi, June 2004), which are jointly organized by CESifo and the Department of International and European Economic Studies of the Athens University of Economics and Business. The CESifo-Delphi Conferences are organized every two years and involve a two-stage process. Following an initial call for abstracts, a number of authors were selected and invited to present their papers at a workshop meeting in Munich. After further refereeing, some of the authors were invited to present (possibly revised) versions of their papers at the final conference meeting in Delphi. Contributions to Economic Analysis was established in 1952. The series purpose is to stimulate the international exchange of scientific information. The series includes books from all areas of macroeconomics and microeconomics.
The EU budget : how much scope for institutional reform? / Raymond Ritter -- From the stability and growth pact to a sustainability council for EMU / Jurgen von Hagen -- Supervision of the European banking market / Martin Schuler -- Reasons and implications of inflation differentials within the European monetary union / Michael Ehrmann -- Black tie required? How to enter a currency union / Volker Nitsch -- Designing Europe : a survey of tasks ahead / Thomas Moutos -- In praise of the European constitution : a political economics perspective / Gerard Roland -- Institutional aspects of EU organization : an economic analysis / Massimo Bordignon -- Welfare policy integration inconsistencies / Giuseppe Bertola.
"This volume is based on papers delivered at the second CESifo-Delphi conferences (Munich, November 2003, and Delphi, June 2004)"--Pref.
Includes index.
Description based on print version record.
Keywords: Business & Economics -- International -- Economics; International economics; EU & European institutions; European Union countries -- Economic policy; European Union countries -- Politics and government